Deconstructing Secular Humanism: Toward an Ethical Islamic Political Philosophy - Muh. Alwi Parhanudin (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This article addresses the research question: Does excluding spiritual foundations from political philosophy undermine justice and legitimacy in modern societies? The primary aim is to critically compare secular and Islamic humanism to clarify their ethical frameworks. As commonly practiced in Western political thought, secular humanism centers on human autonomy and procedural rationality while often marginalizing spiritual and metaphysical perspectives. This orientation, the article argues, leads to a crisis of meaning and normative fragmentation, reducing politics to a technocratic process devoid of ethical depth. In contrast, Islamic humanism—or al-Insāniyyah ar-Rūḥiyyah—roots human dignity in concepts such as divine trust (amānah), servanthood (ʿubūdiyyah), and justice (ʿadālah), integrating ethical responsibility and spiritual purpose into the heart of political life. Methodologically, the study employs a normative-philosophical analysis, drawing from the works of Taha Abdurrahman, Al-Fārābī, and Al-Māwardī, to construct a comparative framework. The findings demonstrate that incorporating spiritual anthropology is not simply a theological issue but an epistemic necessity for achieving meaningful justice. Ultimately, the article offers a conceptual model for reconstructing political ethics, bridging rational and spiritual dimensions to advance a more just and coherent political order.